Smoke-free legislation and childhood hospitalisations for respiratory tract infections - Been, Jasper V.; Millett, Christopher; Lee, John Tayu; van Schayck, Constant P.; Sheikh, Aziz (The European respiratory journal, 2015)
Second-hand smoke exposure is a major risk factor for respiratory tract infections (RTIs). Although evidence suggests important early-life health benefits of smoke-free public environments, the impact on childhood RTIs is unclear. We investigated the association between England's smoke-free legislation and childhood RTI hospitalisations. We used the Hospital Episode Statistics database to obtain nationwide data on hospital admissions for acute RTIs among children (<15 years of age) from 2001 to 2012. Hospitalisation counts were disaggregated by month, age group, sex and small-area level, and linked to urbanisation, region, deprivation index and corresponding population estimates. Negative binomial regression analyses were adjusted for confounders, seasonal variation, temporal autocorrelation, population-size changes and underlying incidence trends. Models allowed for sudden and gradual changes following the smoke-free legislation. We performed sensitivity and subgroup analyses, and estimated number of events prevented. We analysed 1 651 675 hospital admissions. Introduction of smoke-free legislation was followed by an immediate reduction in RTI admissions (−3.5%, 95% CI −4.7– −2.3%), this mainly being attributable to a decrease in lower RTI admissions (−13.8%, 95% CI −15.6– −12.0%). The reductions in admissions for upper RTI were more incremental. The introduction of national smoke-free legislation in England was associated with ∼11 000 fewer hospital admissions per year for RTIs in children.